Spherical molybdenum powders prepared by pulse laser wire cutting - WANG Shi-ze; ZHAO Xing-ke; ZHAO Zeng-lei; WU Ping (Fenmo yejin jishu)
To obtain the high performance solid spherical molybdenum powder raw materials, the spherical molybdenum powders were prepared by the pulse laser wire cutting. The particle size, morphology, microstructure, and other physical properties of the molybdenum powders were studied by sieving, optical microscope, and scanning electron microscope, respectively. The results show that the morphology of molybdenum powders prepared by the pulse laser wire cutting is spherical or nearly spherical, and the surface is smooth without the satellite particles or particle aggregation. In the range of the experimental process parameters, more than 90% molybdenum powder particles are over 150 µm in size, and the particles in the range of 150~300 µm account for the largest proportion, more than 60%. Molybdenum particles with the particle size less than 400 µm are usually internally dense, while the internal holes appear in some larger particles. The formation mechanism of molybdenum particles and internal holes is preliminarily analyzed.